Lived Religion in English Convents in Exile, 1600 - 1800: Accommodating the Ordinary and the Exceptional within the Rule - Caroline BOWDEN (E-REA)
Conventual life in the early modern English communities in exile strictly observed the Rule and Constitutions which governed each house. These not only set out in great detail how every part of the day was to be spent but specified the spirit in which both lay sisters and choir nuns were to approach their tasks: all their time was devoted to God in a spirit of humility. Obituary notices commend many nuns for their assiduity in complying with these strictures, often over very long lives. Nevertheless, there was room for individuality provided it was expressed in the right spirit. This paper examines some examples of how the unusual co-existed with everyday life in a monastic setting.